Urban Life-Worlds in Motion : African Perspectives. - Hahn, Hans Peter (transcript Verlag, 2014)
Urban agglomerations host the most vital and creative societies. This applies particularly to Africa, where cities have the highest growth rates world-wide and where the urban population is younger than anywhere else. Urban life-worlds are the basis for the development of new lifestyles and new cultural phenomena. Based on empirical ethnographic research, this book presents case studies that enhance our understanding of the dynamics of urbanity in Africa and beyond - by envisioning cities as crossroads where cultures, biographies and networks meet. Rezension Reviewed in: UniReport, 4.